2015
DOI: 10.1186/s13104-015-1277-7
|View full text |Cite
|
Sign up to set email alerts
|

Detection of a TRAF1-ALK fusion in an anaplastic large cell lymphoma patient with chemotherapy and ALK inhibitor-resistant disease

Abstract: BackgroundThe anaplastic lymphoma kinase (ALK) gene encodes a receptor tyrosine kinase, which was first identified as the fusion partner of the nucleophosmin (NPM1) gene in the recurrent t(2;5)(p23;q35) found in a subset of anaplastic large cell lymphoma (ALCL). Several distinct, non-NPM1, ALK fusions have subsequently been described in lymphomas and other tumor types. All of these fusions result in the constitutive expression and activation of ALK and ALK signaling pathways, ultimately leading to the malignan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 8 publications
0
9
0
Order By: Relevance
“…There is only one fusion of the TRAF1 gene detected in human cancers, the TRAF1-ALK fusion that has been detected in five patients with anaplastic large cell lymphoma (ALCL) ( 16 19 ). All five cases contain the identical in frame fusion of TRAF1 and ALK that generates a chimeric protein linking the N-terminal 1–294 aa of TRAF1 to the entire intracellular domain of ALK (1,058–1,620 aa), including its kinase domain ( 16 19 ).…”
Section: Traf1mentioning
confidence: 99%
See 1 more Smart Citation
“…There is only one fusion of the TRAF1 gene detected in human cancers, the TRAF1-ALK fusion that has been detected in five patients with anaplastic large cell lymphoma (ALCL) ( 16 19 ). All five cases contain the identical in frame fusion of TRAF1 and ALK that generates a chimeric protein linking the N-terminal 1–294 aa of TRAF1 to the entire intracellular domain of ALK (1,058–1,620 aa), including its kinase domain ( 16 19 ).…”
Section: Traf1mentioning
confidence: 99%
“…There is only one fusion of the TRAF1 gene detected in human cancers, the TRAF1-ALK fusion that has been detected in five patients with anaplastic large cell lymphoma (ALCL) ( 16 19 ). All five cases contain the identical in frame fusion of TRAF1 and ALK that generates a chimeric protein linking the N-terminal 1–294 aa of TRAF1 to the entire intracellular domain of ALK (1,058–1,620 aa), including its kinase domain ( 16 19 ). Interestingly, expression of the TRAF1-ALK fusion protein leads to constitutive activation of the ALK and NF-κB pathways as demonstrated by the elevated levels of phosphorylated ALK (pALK) and STAT3 (pSTAT3) as well as nuclear p50 NF-κB1 and p52 NF-κB2 in ALCL cells ( 18 ).…”
Section: Traf1mentioning
confidence: 99%
“…Thus, it was hypothesized that the TRAF1-ALK fusion pattern has different sensitivities to TKIs. Exons 7 and 8 of the TRAFI gene fused to exon 20 of the ALK gene identi ed in our patients has not been reported, while exons 5 and 6 of the TRAF1 gene fusion were reported recently [29][30][31] . In general, different kinds of fusion genes may be involved in distinct pathways or mechanisms that in uence the outcomes of patients.…”
Section: Discussionmentioning
confidence: 49%
“…The patient was successfully treated with high-dose chemotherapy and ASCT. Another case report presented a 32-year-old male patient who failed autologous transplantation and crizotinib treatment 30 . Similar to our patients, an improvement was observed 3 months after starting crizotinib, but he failed subsequent treatment, indicating that TKI activity is short in these patients.…”
Section: Discussionmentioning
confidence: 99%
“…[200][201][202][203][204][205][206] In a pediatric phase I trial evaluating crizotinib for refractory solid tumors or ALCL, seven of nine (78%) patients with ALK-positive ALCL achieved CR. 207 Gambacorti-Passerini et al reported nine adult patients with refractory ALK-positive ALCL treated with crizotinib.…”
Section: Alk Inhibitorsmentioning
confidence: 99%